The impacts of the new Normative Instruction No. 113, dated December 16, 2020, on the welfare and production of swine - Silva, Júlia Martina da Rocha; Medeiros, Silvana Lúcia dos Santos; Almeida, Alexander Alexandre de; Valentim, Jean Kaique; Moraleco, Débora Duarte (Revista de Ciências Agroveterinárias, 2024)
Pig farming plays a crucial role both in the economic and social aspects, driving the market and generating significant employment. Animal welfare is an increasingly relevant issue in the context of animal production, and in this regard, the publication of Normative Instruction No. 113 on December 16, 2020, represents a significant milestone in promoting animal welfare in the swine industry. This study aimed to conduct a literature review on Normative Instruction No. 113, highlighting its key points and its impact on the swine sector. The research was based on applied research with a descriptive approach, including qualitative literature reviews. In addition, studies related to topics covered in the regulation, such as housing, facilities, and equipment, handling, human-animal relationship, and environmental enrichment, were reviewed. The selection of works focused on studies published recently, covering the period from 2010 to 2022. It is evident that animal welfare is an issue that requires ongoing attention and improvement in production sectors, including swine farming. Normative Instruction No. 113 plays a fundamental role in establishing guidelines aimed at improving rearing conditions and promoting the welfare of pigs. Adequate training and education of professionals involved in the swine industry are crucial aspects to ensure the effective implementation of these guidelines, thus contributing to more ethical and high-quality production.